CTA DIRECTOR REAPPOINTED - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
At their meeting on 13 July 1990, the ACP-EEC Committee of Ambassadors re-appointed Mr D Assoumou Mba, Director of the Technical Centre for Agricultural and Rural Cooperation (CTA), for a further period of the years. Mr Assoumou Mba has been the...